2022
DOI: 10.3390/su15010068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Knowledge Management on Business Processes: Value-Added and Sustainability Perspectives

Abstract: Knowledge management (KM) practice is increasingly less considered as a supportive activity, as knowledge management processes (KMP) are inseparable from critical business processes (BP). Even though some scientific studies underlined that KM integration into BP are expensive and slow due to many organizational barriers, their sustainable value to organizations is undeniable. Although KMPs’ interactions have been studied in the scientific literature, there is still a lack of comprehensive studies related to kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 72 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…According to Kokins and Straujuma (2020), it is essential to have a synergistic approach to BPM and KM, taking into account both social and communicative aspects, as well as cooperation in the scope of integrating KM within BPM (Atkociuniene et al ., 2022). Only then is it possible to fully use the potential which rests in the intellectual capital of knowledge workers (Fleischmann et al ., 2013; Hauder et al ., 2014; Rangiha and Karakostas, 2015; Kerpedzhiev et al ., 2016; Moattar et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kokins and Straujuma (2020), it is essential to have a synergistic approach to BPM and KM, taking into account both social and communicative aspects, as well as cooperation in the scope of integrating KM within BPM (Atkociuniene et al ., 2022). Only then is it possible to fully use the potential which rests in the intellectual capital of knowledge workers (Fleischmann et al ., 2013; Hauder et al ., 2014; Rangiha and Karakostas, 2015; Kerpedzhiev et al ., 2016; Moattar et al.…”
Section: Resultsmentioning
confidence: 99%
“…According to Kokins and Straujum (2020, p. 71), “knowledge and process management, when managed separately, can lead to split focus and resources in the organization, reduce their competitive edge and mismanage their intellectual capital, compared to companies that focus on satisfying their customer requirements”. A synergetic approach to KM and BPM, the integration of BPM and KM will be, or perhaps already is the key instrument of the improvement of the efficiency, productivity and stability of the organization (Atkociuniene et al ., 2022). However, it crucial to strike a balance between structured processes for repeatable aspects of operation and unstructured processes, which require dynamic management, particularly kiBPs (Hauder et al ., 2014; Kerpedzhiev et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Krajnovic [34] examined this topic in a similar market (Croatia) and found that establishing protocols for validating the relevance and reliability of acquired knowledge enhances the overall quality of the organizational knowledge base. This directly affects the level of company competitiveness, as discovered by Kiptalam [35].…”
Section: Process Capability For Knowledge Management Adoptionmentioning
confidence: 99%
“…Knowledge management has an integrated impact on the perspectives of sustainable development in economic, environmental, and social dimensions (Centobelli, Cerchione & Esposito, 2019). Knowledge is often identified as a strategic resource related to the sustainable functioning of an organization, and the knowledge-based view of the organization emphasizes that a successful change to a sustainable business model requires the implementation of the principles of sustainable development and disseminating them throughout the organization's activities and business processes (Atkočiūnienė, Gribovskis & Raudeliūnienė, 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 99%